Impacts of industrialization on rural employment in Nghi Son economic zone, Tinh Gia District, Thanh Hoa Province - Quynh, Doan Thi Nhu (International Journal of Humanities and Education Development (IJHED), 2023)
This research focuses on the impact of industrialization on rural employment in Nghi Son economic zone where has been seen as an important southern economic zone of Than hoa province which was built in 2006 and included 12 communes. The cultivated land that is seen as a crucial tool for the survival of peasants was dispossessed for building numerous factories to establish a new industrial town. Although industrialization has created a wide range of jobs for residents, the peasants are not able to catch up with the strong development of economic development. the industrial enterprises were not employed all redundant labor of Hai Yen commune. So, farmers obviously fell into unemployment situation as an obvious result.